THE LANDUSE CHANGE RELATED TO THE INCREASE OF PEAK DISCHARGE OF PENGABUAN CATCHMENT, JAMBI, INDONESIA - Agus Maryono (Indonesian Journal of Geography, 2009)
Catchments area is an ecosystem unit formed by several components influencing each other. Hence, if one of the components changes, it will influence the others. The objective of this study is to prove the influence of land use change on the increase of the flood discharge with the case study of the catchments area of Pangabuan River, Jambi Province. The decline of secondary forest area occurred from 1665.38 1an2in 1989 to 632.42 1an2in2007. A software simulation program for rainfall-runoff HEC-HMS was used to simulate the increase in the river flood discharge (i.e. sub-catchments area A is from 2677 m31secondin 1989 became 2988.3 m31secin 2007). Based on the land use change from 1989 to 2007, the study predicted the increase of flood discharge by 3148.50 m31sec in 2015. Conservation of the Pengabuan catchments area is needed to minimize the land use change, i.e. primeval forest and secondary forest, primarily in upstream region where large primeval and secondary forests are found.